ChemInform Abstract: Aerobic Photooxidative Synthesis of 2‐Aryl‐4‐quinazolinones from Aromatic Aldehydes and Aminobenzamide Using Catalytic Amounts of Molecular Iodine. Issue 52 (10th December 2015) - Nagasawa, Y.; Matsusaki, Y.; Nobuta, T.; Tada, N.; Miura, T.; Itoh, A.
Abstract: The reaction is conducted by visible light irradiation.